A study on physico-chemical properties of modified sulfur concrete - Amanova, N.D.; Turaev, Kh.Kh.; Djalilov, A.T.; Nomozov , A.K.; Sottikulov, E.S.; Makhmudova , Y.A. (Recent Contributions to Physics, 2024)
In this article, the polymerization reaction of elemental sulfur with organic modifiers is studied, and the optimal conditions of the modification process are presented. Also, the process of obtaining polymer sulfur concrete from modified sulfur is presented. Initially, elemental sulfur is heated to a temperature of 140-145 0C, aniline hydrochloride is added, and the temperature of the reaction is raised to 160 0C for 45 minutes. The average density of this obtained sulfur concrete sample was 2382 kg/m3. Sulfur-based concrete was obtained using the modified sulfur obtained in this process. Sulfur-based concrete was obtained by taking 56% sand, 14% ash, and 30% modified sulfur. Physico-chemical properties of sulfur concrete obtained based on modified sulfur and modified sulfur were studied and analyzed using X-ray phase analysis, IR-spectroscopy, scanning electron microscope, gamma-spectroscopy, and X-ray analysis. Also, the thermal analysis of modified sulfur-based concrete was studied using differential-thermal and thermogravimetric analysis. It was calculated that the average particle size d(nm) of the obtained polymer sulfur concrete is equal to 84.14 according to the Debaya-Sherrera equation.